The impact of Orðaheimurinn language intervention on the vocabulary of monolingual and multilingual Icelandic-speaking preschoolers: Findings of a CRCT - Bryndís Bergþórsdóttir 1994- (2024)
Multilingual children have been shown to be at a disadvantage in the Icelandic school system, with Icelandic language skills lagging significantly behind their Icelandic-speaking monolingual peers and the gap widening with age. As a result, this growing group of culturally and linguistically diverse children faces difficulties participating fully in education. Many teachers report that they lack the skills and knowledge to support multilingual learners in their classroom and the lack of evidence-based interventions at the preschool level in Iceland means that preschools and preschool teachers have limited resources to draw upon in their practice. Therefore, there is an urgent need to examine the appropriateness and effectiveness of interventions with an established evidence base for accelerating the language development of multilingual children in Icelandic preschools. In this thesis, I investigated the impact of 18 weeks of intervention using Orðaheimurinn (OH), the culturally and linguistically adapted World of Words (WOW) programme, which has been recognised as having good effectiveness and a high level of evidence in the United States. OH is a soft-structured teacher-led intervention that aims to improve the development of vocabulary and concept knowledge of 4-year-old monolingual and multilingual Icelandic-speaking preschoolers. The intervention utilises shared-reading interactions, teaches vocabulary in taxonomic categories within a meaningful context, and encourages active participation by the children. A subset of data collected for the larger Orðaheimurinn cluster-randomised controlled trial was used in this study. Data included in this research was drawn from parent surveys, standardised assessment of language skills (MELB) and researcher-designed probe tasks of curriculum-based receptive vocabulary, concept knowledge, and categorical property. Data from 110 children across 10 preschools, divided into OH and Control arms, was collected before and immediately following an 18-week intervention period. ...